Upaya Peningkatan Kesejahteraan Ekonomi Masyarakat Desa melalui Industri Rumahan Gerabah, Studi Kasus di Desa Maregam Kecamatan Tidore Selatan, Kota Tidore Kepulauan - Hamisi, Nuria; HS, Nur Azizah; Radjaloa, Vhyda Hamidah Aulia (Peneliti.net, 2024)
Maregam is one of the villages in North Maluku where the people have creativity as craftsmen using soil, the local people call it